Optimization process for enhancing the recovery of ammonium and phosphate from wastewater by modified rice husk biochar - Thanh, Nguyen Lan; Nguyet, Nguyen Le Huong; Le, Van Giang; Thuy, Nguyen Thi; Phong, Vo Hoang Nhat; Que, Vo Nguyen Xuan; Hang, Vo Thanh; Huy, Nguyen Nhat (Engineering and Applied Science Research, 2023)
This study aimed to optimize the recovery of ammonium and phosphate from wastewater using Mg-modified biochar as an adsorbent. Given the situation of domestic wastewater and agricultural waste in Vietnam, the researchers fabricated biochar from rice husk and modified it with magnesium salt to make it an effective material for wastewater treatment. To determine the optimal conditions for the experiments, the response surface methodology was used, specifically the central composite design (CCD) model with four factors, namely biochar dosage (g/L), pH, N:P ratio, and initial concentrations of NH4+ and PO43-. The material was thoroughly characterized using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) to ensure that it met the desired specifications. Based on the experimental design, the optimal conditions were determined to be a biochar dosage of 0.12 g/L, an N:P ratio of 1.25, an initial concentration of 60 mg/L, and a pH of 6. Tests conducted in synthetic wastewater produced results that were in agreement with the predicted values. However, when the optimized values were tested in domestic wastewater, only phosphate removal showed good agreement with an efficiency of 93% compared to the predicted optimization value of 88%. This study demonstrates the potential of Mg-modified biochar as an effective adsorbent for recovering ammonium and phosphate from wastewater. Although further optimization may be required for ammonium removal in domestic wastewater, the results are promising and warrant further investigation.